Leadership Culture Efforts to Strengthen Teacher Professionalism at MTs Negeri Luwu Utara - Putri Vista; Sukirman Sukirman; Munir Yusuf (International Journal of Educational Administration, Management, and Leadership, 2024)
This study examines the role of transformational leadership by the madrasah principal in shaping school culture and enhancing teacher professionalism at MTs Negeri Luwu Utara. A qualitative approach was employed, using a case study method, with data gathered through in-depth interviews, observations, and document analysis. The findings show that the principal's leadership style includes elements of directive, supportive, participatory, and achievement-oriented approaches, demonstrating an adaptive method tailored to the institution's needs. School culture is built through teacher involvement in decision-making, open communication, innovation, and adequate performance supervision. Teacher professionalism is strengthened through providing challenges, ongoing professional development, sufficient facilities, and motivation and recognition from school leadership. Leadership values such as consistency, a future-oriented vision, collaboration, role modeling, and caring are key drivers in fostering a positive school culture and improving teacher professionalism. The connection between leadership, school culture, and teacher professionalism is mutually reinforcing, creating an educational environment that is supportive, collaborative, and focused on enhancing the quality of teaching and learning. This study recommends strengthening transformational leadership as a strategic approach to elevate the quality of madrasah education.